2000
DOI: 10.1208/ps020218
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of acetaminophen and indocyanine green in cystic fibrosis-knockout mice

Abstract: Drug treatment poses a therapeutic challenge in cystic fibrosis (CF) because the disposition of a number of drugs is altered in CF. Enhanced clearance of acetaminophen (APAP) and indocyanine green (ICG) have previously been reported in CF patients. The objective of the current study was to investigate if the CF-knockout mouse model (cftr m1UNC ) shows altered pharmacokinetics similar to those seen in CF patients using the 2 model compounds APAP and ICG. Clearance (CL/F) of APAP and renal (CL R ) and formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The clearance of ICG has been previously examined as a functional marker in experimental models of liver injury or toxicity [12,13,27–29]. Inage et al [6] examined the pharmacokinetics of ICG in rats with partial hepatectomy and in rats with fibrosis secondary to carbon tetrachloride toxicity and found that the clearance of ICG correlated with the functional reserve and liver mass [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clearance of ICG has been previously examined as a functional marker in experimental models of liver injury or toxicity [12,13,27–29]. Inage et al [6] examined the pharmacokinetics of ICG in rats with partial hepatectomy and in rats with fibrosis secondary to carbon tetrachloride toxicity and found that the clearance of ICG correlated with the functional reserve and liver mass [6].…”
Section: Discussionmentioning
confidence: 99%
“…The method was adapted from Kulkarni et al [12] and validated in our laboratory. A Waters C 18 symmetry column equipped with a guard column (Waters Associates, Milford, MA) was used for reverse-phase chromatography at a temperature of 35° C. The mobile phase consisted of 50 mM potassium phosphate buffer (pH 5.52): acetonitrile (55:45), at a flow rate of 1.0 ml/min and 17-minute run time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others are as follows: clay content, r = 0.03-0.38; organic matter content, r = 0.12-0.48; CEC, r = 0.13-0.27. Kinney et al (2006) have reported that although having high water solubility (12,900 mg/L) (Chen et al 2002), high pK a (9.4-9.5) (Dasmalchi et al 1995;Kulkarni and Pegram 2000), and low log K ow (Snyder et al 2003), acetaminophen accumulated in soil as much as other pharmaceuticals (erythromycin, carbamazepine, and fluoxetine) with low water solubility less than 100 mg L -1 and relatively high log K ow did. Like acetaminophen, all the SSRIs had high water solubility (3,022-15,460 mg/L), high pK a (9.39-10.32) (Vasskog et al 2006), and low log K ow (1.12-1.39).…”
Section: Ssrimentioning
confidence: 99%
“…Another difference of murine CF models as compared to humans concerns drug clearance [123]. Mice are also available which over-express the sodium channel EnaC and show CF like lung disease [124].…”
Section: Which Animal Models Are Useful For Drug Testing?mentioning
confidence: 99%